2018
DOI: 10.1101/273599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SpiceRx: an integrated resource for the health impacts of culinary spices and herbs

Abstract: Spices and herbs are key dietary ingredients used in cuisines across the world. They have been reported to be of medicinal value for a wide variety of diseases through a large body of biomedical investigations. Bioactive phytochemicals in these plant products form the basis of their therapeutic potential as well as adverse effects. A systematic compilation of empirical data involving these aspects of culinary spices and herbs could help unravel molecular mechanisms underlying their effects on health.SpiceRx pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this study, we define phytochemicals as compounds of plant or food origin. Data regarding the phytochemicals and their sources were curated from open-source databases, including KNApSAcK, 44 FooDB, 45 Phenol-Explorer, 46 NPASS, 47 TCMID, 48 SpiceRX, 49 and DietRX. 50 After removing duplicates and small molecules with SMILES lengths less than ten characters, we obtained 84 650 phytochemicals and 45 367 sources.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we define phytochemicals as compounds of plant or food origin. Data regarding the phytochemicals and their sources were curated from open-source databases, including KNApSAcK, 44 FooDB, 45 Phenol-Explorer, 46 NPASS, 47 TCMID, 48 SpiceRX, 49 and DietRX. 50 After removing duplicates and small molecules with SMILES lengths less than ten characters, we obtained 84 650 phytochemicals and 45 367 sources.…”
Section: Methodsmentioning
confidence: 99%
“…Their antioxidant, anti-inflammatory and immunomodulatory properties are well documented (Gupta 2010;Yashin et al 2017;Jiang 2019). The health impacts of culinary spices and herbs have been compiled as a structured database -SpiceRx (https://cosylab.iiitd.edu.in/ spicerx/), and is available in the public domain (Rakhi et al 2018). Their vital role in enriching flavor, improving digestion, and supporting human health by way of their antioxidant and immune boosting properties is much discussed during this pandemic.…”
Section: Spices and Covid-19mentioning
confidence: 99%
“…[10] 'Spicerx', an extensive evidence-based database regarding spices, their constituents and health benefits has also been recently compiled. [11] Elsayed & Khan have analyzed COVID-19 records for first wave from 163 countries and revealed a clear correlation of its incidence, recovery rate and mortality rate with their spice consumption. [11] They have reported that total number of cases and mortality were lower in countries with high spice consumption.…”
Section: Introductionmentioning
confidence: 99%